Hubungan Pola Asuh Orang Tua Dengan Prestasi Akademik Siswa - Hadi Wijaya; Nurussa’adah; Akhmad Muzakkir (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The purpose of this study was to determine the relationship between parenting patterns and academic achievement of fifth-grade students of SDN 1 Sandik, Batulayar District, West Lombok Regency. The data source of this study was 22 fifth-grade students. Data collection was carried out using observation, questionnaires, and documentation methods. Furthermore, the data obtained were analyzed using Pearson product moment correlation test analysis. In order to determine the relationship between parenting patterns and academic achievement. The results of the study showed that there was a significant relationship between parenting patterns and student academic achievement. The results showed that: positive and supportive parenting patterns from parents tend to encourage students to achieve better academic achievement, less supportive parenting patterns can hinder achievement, active parental involvement in accompanying children studying at home is an important factor in improving student academic achievement.